EKSEKUSI RIIL TERHADAP PUTUSAN HAKIM YANG TELAH MEMPUNYAI KEKUATAN HUKUM TETAP PADA PERKARA PERDATA NO.20/P.dt.G/2011/PN.Pbr DI PENGADILAN NEGERI KELAS IA PEKANBARU - NURI JUMAIDAH AULIA; Mardalena Hanifah; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Research a civil dispute in two ways, namely litigation and noon-litigation. Dispute resolution throught litigation ended with the judge's decision that has legally binding (inkracht van gewijsde) So in the implementation of the judge’s decision forcible (real execution) by the executor of execution with the help of the public such as the police, even though the military. The real execution is done by district courts often me with resistance from the parties executed a decision of the judge, so many factors that can disturb process of execution. Based on the authors are interested in doing reseaech titled “Real Execution on Civil Case No.20/Pdt.G/2011/pn.Pbr at IA Class of District Court Pekanbaru”. The aimed of this researct was the first, to know the realexecution in civil case on No.20/Pdt.G/2011/PN.Pbr at IA Class of District Court Pekanbaru and secondly, due to the law, which caused when one of the parties was not present in the process the real execution in on No.20/Pdt.G/2011/PN.Pbr at IA Class of District Court Pekanbaru. The first problem was, how real execution civil case on NO.20/P.dt.G/2011/PN.P.br at IA Class of Pekanbaru Court, second, what as a result of the law of the absence of the parties at the time of the execution. This research used juridical sociological research that was descriptive. The research location was in IA Class of Pekanbaru Court. The data used primary data and secondary data as well as data collection techniques such as interviews and library research. From the results of research that was conducted on the first problem can be concluded that at the stage before the execution of district court Pekanbaru has carried out the procedure properly andcorrectly in accordance stipulated by law. At the time of the executions carried out procedures that do not conform to the minutes that have been assigned that cause frustration for the executed. Should the court conducting the execution in accordance with what has been set. The second problems can be concluded that the parties in the case that plaintiff and defendant attend when execution process. Party of National Land Agency of Pekanbaru as the surveyor was not present at the executions carried out. However National Land Agency was not attend, the execution wiil be conducted.Keywords: Real Execution, Civil Case, Class IA of District Court Pekanbaru